The Impact of 2013 haze on emergency department utilizations for acute respiratory diseases: a retrospective study - Mohd Azim Ab Manap,; Shamsuriani Md Jamal,; Hilwani Kaharuddin,; Husyairi Harunarasid,; Mazrura Sahani,; Talib Bin Latif,; Nik Azlan Nik Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Haze imposes a substantial health burden especially in Southeast Asia where occurrences are frequent. Reduction in air quality levels has resulted in an increase in healthcare utilization, especially to the front door of healthcare, the emergency department (ED). Data on ED utilization during haze period is lacking. This was a retrospective study aimed to determine the association between haze and ED utilization of haze-related acute respiratory illnesses between April 2013 to September 2013. The study period was divided into haze/ non-haze period. Clinical data was collected from the registration book and patients’ case notes. Environmental data was obtained from Institute of Environment and Development Universiti Kebangsaan Malaysia. Total number of patients presented to ED during the study was 32,661. Fifteen percent (n= 5177) presented with acute respiratory symptoms. Total Emergency Department visits during haze period reduced due to emergency declaration, hence reducing non-emergency visits. However, there was a significant increase in hospital admission (p=0.0015) and infective respiratory illnesses (p=0.001) during haze which correlates with increase air pollutant. Patients with chronic respiratory illnesses were more affected by haze (p = 0.001). PM10 and ozone were the main pollutant during the haze period. Increasing pollutant levels from the haze significantly increases ED hospital admission. Evidence from this study can influence policymakers to prepare and allocate resources to hospitals in response to haze-related illnesses.